2020
DOI: 10.1186/s12967-020-02621-4
|View full text |Cite
|
Sign up to set email alerts
|

Tespa1 plays a role in the modulation of airway hyperreactivity through the IL-4/STAT6 pathway

Abstract: Background Thymocyte-expressed, positive selection-associated 1 (Tespa1) is a critical signaling molecule in thymocyte development. This study aimed to investigate the regulatory effect of Tespa1 on mast cells in the pathogenesis of asthma and its relationship with the interleukin (IL)-4/signal transducers and activators of transcription 6 (STAT6) signaling pathway. Methods Tespa1 mRNA expression analysis and IgE levels were carried out using the i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…TESPA1 is involved in the development and maturation of T-cells and plays a critical role in immune defects in the elderly [ 62 ]. Furthermore, animal models have shown that TESPA1- knockout mice ( Tespa1 −/− , KO) exhibit more severe inflammation [ 63 ]. Given that a critical component of aging is a set of functional and structural changes in the immune system that manifests in reduced B and T cell production [ 62 ], genetic variation in TESPA1 might influence the aging process.…”
Section: Discussionmentioning
confidence: 99%
“…TESPA1 is involved in the development and maturation of T-cells and plays a critical role in immune defects in the elderly [ 62 ]. Furthermore, animal models have shown that TESPA1- knockout mice ( Tespa1 −/− , KO) exhibit more severe inflammation [ 63 ]. Given that a critical component of aging is a set of functional and structural changes in the immune system that manifests in reduced B and T cell production [ 62 ], genetic variation in TESPA1 might influence the aging process.…”
Section: Discussionmentioning
confidence: 99%
“…BALB/c and C57BL/ 6 mice are commonly used as model animals for allergic rhinitis. [2][3][4] However, when given identical sensitization and challenge protocols, the two types of mice exhibit different levels of airway responsiveness. 5 For example, BALB/c mice developed more severe allergic rhinitis than the C57BL/6 mice when the Schistosoma mansoni egg was used.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Tespa1 is reported to be involved in the regulation of the proliferation and function of B cells probably via the CD40/TRAF6 axis [ 21 ]. Recent researches show that Tespa1 also participates in the activation of mast cells, thereby modulating allergic response and airway hyperreactivity [ 22 , 23 ]. These findings indicate that Tespa1 is a crucial regulator of the immune system.…”
Section: Introductionmentioning
confidence: 99%